PENGARUH EXPERIENTIAL MARKETING TERHADAP KEPUASAN PELANGGAN (Studi Kasus Bioskop Cinema XXI Ayani Pontianak) - B11110153, SUPRIYANA (Jurnal Manajemen Update, 2015)
This research aimed to analyze the influence of experiential marketing which includes a variable sense, feel, think, act, and relate to customer satisfaction of Cinema XXI Ayani Pontianak. This research was designed as an descrptive and causal. The population of this research is the customer of Cinema XXI Ayani Pontianak who have been watching at least 1 times and minimum 17th years old. This research was using accidental sampling, then elected a sample size of 100 people. The analysis technique used multiple linier regression analysis by SPSS version 20.0. The results based on multiple linier regression analysis showedthat sense, feel, think, act and relate as part of experiential marketing together or simultaneously positive and significant effect on customer satisfaction with the R2 value of 58.6%, while the remaining 41.4% is another factor not examined in this research. Through t-test, sense, feel, think, and act in partial positive and significant effect on customer satisfaction, relate partially positive but not significant effect on customer satisfaction. Keywords : experiential marketing, sense, feel, think, act, relate and customer satisfaction.